A feira livre de Porto Nacional-TO: espaço de comercialização, socialização e resgate cultural - Branco, Lesley Cristina Araujo Castelo (Universidade Federal do Tocantins, 2022)
This work was developed in the city of National -To Port , aiming to investigate the socio- economic relations within the geographical area of municipal street market of the city.